Optimal timing for discontinuation of ERCP in cases of difficult selective biliary cannulation - Han Taek Jeong; Jimin Han (Endoscopy International Open)
Background and study aims: Prolonged cannulation during endoscopic retrograde cholangiopancreatography (ERCP) increases risk of complications, particularly post-ERCP pancreatitis (PEP). This study aimed to determine optimal timing to discontinue ERCP when selective biliary cannulation (SBC) cannot be easily achieved. Patients and methods: Patients with naïve papilla who underwent ERCP between January 2021 and December 2021 were analyzed. The primary outcome was to determine optimal timing for discontinuing ERCP based on cannulation success rate and complication rate. Results: A total of 272 patients with naïve papilla underwent ERCP. Trainees did not participate in any of the procedures. Median age was 71 years, and 152 patients (55.9%) were male. The most common indication for ERCP was choledocholithiasis (60.7%), followed by malignant obstruction (24.3%) and benign stricture (4.8%). SBC was achieved in 249 patients (91.5%). After excluding patients with pre-procedure amylase elevation or preexisting pancreatitis, 232 patients were analyzed for complications. Eighteen patients (6.7%) experienced complications, with PEP occurring in 15 patients (5.5%). SBC success was achieved in 50% of cases at 3.3 minutes and in 90% at 12.1 minutes. In contrast, the PEP rate reached 10% after 7.9 minutes and 14.5% after 12.1 minutes. Multivariate analysis identified distal biliary stricture and age over 70 as significant predictors of difficult SBC. Conclusions: In cases of difficult SBC, discontinuing attempts at around 8 minutes may minimize risk of PEP. However, extending attempts up to 12 minutes can be justified to achieve higher success rates. Beyond 12 minutes, likelihood of successful SBC diminishes significantly.